1983
DOI: 10.1203/00006450-198305000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Disaccharide Feedings Enhance Rat Jejunal Macromolecular Absorption

Abstract: Summaryperiods of feeding at lower disaccharide concentrations, which do not induce symp~oms of intolerance. After the high lactose conDisaccharide feedings to post-weaning rats alters their jejunal centration feedings, there was evidence of morphologic damage to barrier to macromolecular absorption. Penetration of horseradish the epithelium of the jejunal mucosa. ~h~ disaccharide-induced peroxidase (HRP) across the jejunum was enhanced after short-increase in HRp absorption may be mediated by transport from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The effect was comparable to total parenteral nutrition 47 . In addition, feeding of disaccharides, especially lactose, increased jejunal permeability to macromolecules in rats 48 . In contrast, Sanderson et al .…”
Section: Mechanisms Modulating Intestinal Permeabilitymentioning
confidence: 82%
“…The effect was comparable to total parenteral nutrition 47 . In addition, feeding of disaccharides, especially lactose, increased jejunal permeability to macromolecules in rats 48 . In contrast, Sanderson et al .…”
Section: Mechanisms Modulating Intestinal Permeabilitymentioning
confidence: 82%
“…In earlier studies, oral lactose (30 g/kg) produced weight loss and osmotic diarrhea to rats, with intestinal barrier leakage, observed by increased jejunal permeability to horseradish peroxidase (HRP) [22]. …”
Section: Discussionmentioning
confidence: 99%
“…In order to evaluate the effect of zinc supplementation on acute diarrhea, lactose-driven osmotic diarrhea was induced to the study rats, as described by Teichberg et al [22]. A subset of undernourished rats that received RBD was also challenged by a saturated lactose solution (monohydratated sodium lactose, Vetec Química, Rio de Janeiro, Brazil), which was given by gavage diluted in 2 mL of PBS, 30 g/Kg, starting on day 8 until day 14 to induce osmotic diarrhea.…”
Section: Methodsmentioning
confidence: 99%
“…Rothman et al [6] have also reported twice the amount of transported BSA in malnourished animals as compared with controls. Enhanced intestinal uptake of macro molecules in protein-deficient animals is prob ably due to increase in pinocytotic activity with deterioration of apical junctions and movement of protein molecules directly be tween the cells [6], Feeding of disaccharides to animals has been shown to increase HRP pen etration across the jejunum in postweaned rats [14], Since LP diet contained high sucrose con tent, it may be an additional factor for the observed increase in protein uptake under these conditions. Further, the effects of etha nol feeding to malnourished rats were opposite to those seen in normal protein (18%) fed rats.…”
Section: Discussionmentioning
confidence: 99%